2012
DOI: 10.1002/anie.201108292
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Planar‐Chiral (η6‐Arene)Chromium Complexes by Molybdenum‐Catalyzed Asymmetric Ring‐Closing Metathesis

Abstract: Planar-chiral (h 6 -arene)chromium complexes are useful chiral scaffolds in asymmetric synthesis, and have found widespread application as chiral ligands for asymmetric catalysis, or as chiral building blocks for natural product syntheses. [1] Typical methods for the preparation of enantiomerically enriched planar-chiral (arene)chromium species are based either on the optical resolution of racemates [2] or on stereoselective transformations, which include diastereoselective complexation, [3] diastereo-or enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 91 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…The reactions were carried out in benzene at 40 °C with an appropriate chiral molybdenum catalyst (10 mol %) that was generated in situ from [(pyrrolyl) 2 Mo(CHCMe 2 Ph)(NC 6 H 3 ‐2,6‐ i Pr 2 )] and an axially chiral biphenol derivative 9. Under these conditions, the Mo/( R )‐ L1 species,10a which was the best catalyst for the kinetic resolution of the planar‐chiral (π‐arene)chromium complexes,7a showed good enantioselectivity (97 % ee ) but insufficient activity (Table 1, entry 1). The Mo/( R )‐ L2 species10b was not effective at all (entry 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were carried out in benzene at 40 °C with an appropriate chiral molybdenum catalyst (10 mol %) that was generated in situ from [(pyrrolyl) 2 Mo(CHCMe 2 Ph)(NC 6 H 3 ‐2,6‐ i Pr 2 )] and an axially chiral biphenol derivative 9. Under these conditions, the Mo/( R )‐ L1 species,10a which was the best catalyst for the kinetic resolution of the planar‐chiral (π‐arene)chromium complexes,7a showed good enantioselectivity (97 % ee ) but insufficient activity (Table 1, entry 1). The Mo/( R )‐ L2 species10b was not effective at all (entry 2).…”
Section: Methodsmentioning
confidence: 99%
“…Plausible stereochemical pathways of the ARCM of 1 are shown in Scheme . Based on our previous studies,5a, c, 7a it is postulated that the initial metathesis between the ( R )‐Mo‐alkylidene catalyst and 1 takes place at the P ‐allyl group, which is the sterically least hindered olefin in 1 , to form intermediate A . The more electron‐donating PR 2 group in 1 (and in A as well) increases electron density at the two isopropenyl groups through the chromium atom and the π‐arene moiety, which eventually facilitates the second metathesis in A .…”
Section: Methodsmentioning
confidence: 99%
“…Among various phosphine‐olefin ligands described in the previous literatures, we have developed planar‐chiral phosphine‐olefin ligands based on ( η 6 ‐arene)chromium(0), which is known as “first‐generation.” The S type first‐generation ligand ( S )‐ 1 gives the R type 1,4‐adducts from cyclic enones and the S type 1,4‐adducts from acyclic enones, respectively (Schemes and ). When ( R )‐1 ligand is employed, the enantiomers of the adducts are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Although an asymmetric metathesis reaction itself does not form as tereogenic carbon atom directly,i th as been demonstrated to control peripheral chirality by kinetic resolution of racemic chiral molecules or desymmetrization of prochiral substrates by the use of ac hiral metathesis catalyst. [11][12][13] Although we have shown how to successfully control the planar chirality in ferrocenes [12] as well as in (p-arene)chromium complexes by asymmetric metathesis reactions, [13] we were challenged to apply the metathesis protocol to the enantioselective synthesis of the winding-vine-shapedc om-pounds.H erein, we report the results of our studies for preparing bisimidazole derivatives 1 in high enantiomeric purity by the molybdenum-catalyzed asymmetric ring-closing metathesis (ARCM). [11][12][13] Although we have shown how to successfully control the planar chirality in ferrocenes [12] as well as in (p-arene)chromium complexes by asymmetric metathesis reactions, [13] we were challenged to apply the metathesis protocol to the enantioselective synthesis of the winding-vine-shapedc om-pounds.H erein, we report the results of our studies for preparing bisimidazole derivatives 1 in high enantiomeric purity by the molybdenum-catalyzed asymmetric ring-closing metathesis (ARCM).…”
mentioning
confidence: 99%
“…However,l ess studies have shown how to control noncarbon centrostereogenicities [10] and non-centrochirality. [11][12][13] Although we have shown how to successfully control the planar chirality in ferrocenes [12] as well as in (p-arene)chromium complexes by asymmetric metathesis reactions, [13] we were challenged to apply the metathesis protocol to the enantioselective synthesis of the winding-vine-shapedc om-pounds.H erein, we report the results of our studies for preparing bisimidazole derivatives 1 in high enantiomeric purity by the molybdenum-catalyzed asymmetric ring-closing metathesis (ARCM).…”
mentioning
confidence: 99%